Anti‐inflammatory and anti‐apoptotic effects of the combination of Ligusticum chuanxiong and Radix Paeoniae against focal cerebral ischaemia via TLR4/MyD88/MAPK/NF‐κB signalling pathway in MCAO rats. (28th November 2017) - Gu, Junfei; Su, Shulan; Guo, Jianming; Zhu, Yue; Zhao, Ming; Duan, Jin‐ao
Abstract: Objective: This study was performed to assess the anti‐inflammatory and anti‐apoptotic effects of the combination of Ligusticum chuanxiong and Radix Paeoniae (XS) on focal cerebral ischaemic stroke. Methods: MCAO rats were used to evaluate the effect of XS on stroke. Cerebral water content was measured, and the levels of IFN‐γ, IL‐1β, IL‐6 and IL‐12 in serum and brain were assessed by ELISA kits. Protein expressions including p‐p38, p‐38, TLR‐4, p‐ERK, ERK, TLR‐5, NF‐κBp65, Myd88, Caspase‐3 and Caspase‐12 were examined by WB and IHC. Q‐PCR was applied to examine IL‐1β and IL‐6 mRNA levels in the rat brain of each group. Key findings: XS treatment remarkedly decreased the levels of IFN‐γ, IL‐1β, IL‐6 and IL‐12 in serum and brain tissues of MCAO rats. In the ischaemic brain, the expressions of TLR‐4, TLR‐5, p‐p38, p‐ERK, Myd88, NF‐κBp65, Caspase‐3 and Caspase‐12 were increased significantly, while the treatment attenuated the activated expressions by MCAO. XS also downregulated Caspase‐3 and Caspase‐12 expressions. IL‐1β and IL‐6 mRNA levels in MCAO brain tissue were decreased by XS treatment. Conclusions: XS could protect MCAO rats by anti‐inflammation and anti‐apoptosis through TLR4/MyD88/MAPK/NF‐κB signalling pathway. Furthermore, the combination has a more meaningful improvement on focal cerebral ischaemic stroke.